Pengembangan Aplikasi â€œDaDi Pinterâ€ Sebagai Media Pembelajaran Berbasis Mobile Learning Pada Materi Fluida Dinamis - Lugas Haryo Pradigdo; Mita Anggaryani (PendIPA Journal of Science Education, 2023)
Learning media has a very vital role in the learning process. Learning media that are in accordance with current learning are technology-based media. Learning by using technology has the advantage of being able to provide learning opportunities anytime and anywhere. This study aims to analyze the results of the validity of the DaDi Pinter application as a media-based learning mobile learning to improve cognitive learning outcomes in dynamic fluid material. This study uses the ADDIE development method. Three stages are used: analysis, design, and development. The analysis phase is carried out by analyzing the material, needs, and habits of students. The design stage is carried out by designing the appearance and content of the DaDi Pinter application. Furthermore, the development stage is carried out by validating and revising the DaDi Pinter application based on input and suggestions from the validator. The validity of the DaDi Pinter application was assessed using a scale likert. Media experts and material experts assess the validity of the DaDi Pinter application. Media validation assessment is seen from the appearance design, program operation, navigation, and usability. Material validation assessment consists of aspects of material quality and material usefulness. The data analysis technique was carried out by calculating the validity results of the DaDi Pinter application from 3 validators. The results showed that the validity of the DaDi Pinter application on the media obtained an average percentage of 96% with a very valid category. The results showed that the validity of the DaDi Pinter application was 98%. Based on the results of this validity, the DaDi Pinter application is very valid and can be used in learning.